Safety of YAG laser vitreolysis for intraocular tissues: analysis of postoperative complications - Liu, Jiannan; Wang, Hao; Gu, Wei; Zhao, Tingting; Fan, Wenxue; Peng, Shaomin (International ophthalmology, 2023)
Purpose To evaluate the safety of yttrium–aluminum-garnet (YAG) laser vitreolysis for intraocular tissues. Methods Thirty-six New Zealand rabbits were divided as follows: Group 1000 (n = 12) treated with YAG laser of 1000 mJ (5 mJ × 200 shots), Group 2000 (n = 12) treated with YAG laser of 2000 mJ (5 mJ × 400 shots), Group 3000 (n = 12) treated with YAG laser of 3000 mJ (5 mJ × 600 shots). Either a single eye was chosen as the study eye in study groups while the other was untreated as the control group. Intraocular pressure (IOP), slit-lamp, optical coherence tomography (OCT), transmission electron microscopy (TEM), and inflammatory cytokines of aqueous humor (interleukin-1α (IL-1α), interleukin-1β (IL-1β), interleukin-8 (IL-8), and tumor necrosis factor-α (TNF-α)) were performed to examine the rabbits. Results There were no abnormalities in the study groups of IOP, slit-lamp, and OCT examinations. Group 3000 of TEM showed: neutrophils and mitochondrial swelling on day 1, and fibroblasts and neocollagen on day 14. No abnormalities were observed in Group 1000 and 2000 of TEM. Levels of IL-1α and TNF-α increased at 12 h and decreased to baseline on day 3. Levels of IL-1β increased at 12 h and decreased to baseline on day 7. Levels of IL-8 increased on day 1 and decreased to baseline on day 3. Conclusion YAG laser vitreolysis is safe when the distance is more than 2 mm from ablation point to the lens and the retina, and the total energy is less than 2000 mJ for one treatment procedure.